Identification and characterization of N‐tert‐butoxycarbonyl‐MDMA: a new MDMA precursor. Issue 3 (29th September 2016) - Collins, Michael; Donnelly, Christopher; Cameron, Shane; Tahtouh, Mark; Salouros, Helen
Abstract : In September 2015, 80 litres of a viscous, light‐red liquid, described as hair product, was seized by the Australian Border Force (ABF). Initial testing by ABF indicated that the liquid was the 3, 4‐methylenedioxymethamphetamine (MDMA) precursor chemical safrole and custody of the material was transferred to the Australian Federal Police (AFP) who coordinated all subsequent investigations. Initial gas chromatography–mass spectrometry (GC‐MS) analysis by the AFP indicated that the material was not safrole and samples of the liquid were transferred to the National Measurement Institute Australia (NMIA) for identification. Using a combination of nuclear magnetic resonance spectroscopy (NMR), GC‐MS, infrared spectroscopy, and synthesis, the unknown substance was identified as N‐tert .‐butoxycarbonyl‐MDMA ( t ‐BOC‐MDMA). The substance was also converted in high yield to MDMA (aqueous HCl, 80 °C, 30 min). The possibility that the t ‐BOC‐MDMA may act as a pro‐drug following ingestion was explored by exposure to simulated gastric juice (pH 1.5) and monitored by NMR (37 °C) at various intervals. The majority of t ‐BOC‐MDMA was converted to MDMA after 305 min, which suggested that this derivatized form might serve as a pro‐drug in vivo . An investigation into the chemistry of potential pro‐drugs showed that t ‐BOC derivatives of methamphetamine, pseudoephedrine and 4‐methylmethcahtinone (mephedrone) could also be prepared using di‐ tert .‐butyl dicarbonate. The appearance of t ‐BOC‐derivatives on the drug market requires further monitoring. © 2016 Commonwealth of Australia. Drug Testing and Analysis © 2016 John Wiley & Sons, Ltd. Abstract : A light‐red liquid seized by the Australian Border Force (ABF) was determined to contain N‐tert ‐butoxycarbonyl‐MDMA using a combination of NMR, GC‐MS, infrared and synthesis. The substance was easily converted in high yield to MDMA.